(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Human resources is one of the factors that play an essential role in the field of tourism, so the quality of education and training is needed to improve the quality of human resources in the tourism industry, which is the leading actor or tourism product. The purpose of this research is to improve the quality of human resources in Samin Traditional Village, to find out the function of education in empowering tourism human resources, and to find out the knowledge of local people about the history of Samin Traditional Village. The method used to write the article in this research is descriptive-qualitative by applying data collection techniques through interviews and observations. The research results show that human resources in Samin Village still need to be higher because there is no self-awareness in the surrounding community. However, they still understand the culture and history of the Samin Tribe. This is evidenced by the need for more development of tourism awareness groups in Samin Village because the average youth migrates to the city. On the positive side, elementary school students already understand the customs and culture in Samin Village, as evidenced by their ability to talk about the village or village they live in in the ’Little Tourist Guide’ program.